Effect of pressure on the physical properties of the superconductor NiBi3. (12th December 2018) - Gati, Elena; Xiang, Li; Wang, Lin-Lin; Manni, Soham; Canfield, Paul C; Bud'ko, Sergey L
Abstract: We present an experimental study of the superconducting properties of NiBi3 as a function of pressure by means of resistivity and magnetization measurements and combine our results with density functional theory calculations of the band structure under pressure. We find a moderate suppression of the critical temperature from K to K by pressures up to 2 GPa. By taking into account the change of the band structure as a function of pressure, we argue that the decrease in is consistent with conventional, electron–phonon-mediated BCS-type superconductivity.